Outcome of spillage of gallbladder contents during laparoscopic cholecystectomy: a case control study - Amin, Ruhul; Ovi, Mir Rasekh Alam; Nasrin, Shamima (International Surgery Journal, 2023)
Background: Bile leakage due to many causes are common during laparoscopic cholecystectomy (LC). We sought to determine prospectively the incidence of gallbladder perforation during LC and to ascertain whether or not spillage of gallbladder contents resulted in overt complications. Methods: Between July 2013 to December 2013, 120 patients underwent LC participated in this study. All patient’s pre-operative ultrasonogram reports were collected. Of the 120 patients, 53 patients had spillage of gallbladder contents due to intra operative perforation. Per operative data were collected. Bile sample of all the hundred twenty patients were sent for culture and sensitivity. All patients were followed-up for two weeks post operatively. Results: Compared with those without GB perforation, there was a larger percentage of men (41.5%) in the spillage group. Spillage also common in patients having acute cholecystitis (32%), pigment stones (26 out of 38 pigment stone), multiple number of stones (77.3%), positive bile culture (30%). Most common complication was port site wound infections (3 in no. out of 53). There was no difference in post-operative amount or type of analgesia administered, duration of post-operative hospital stays in between two groups. Conclusions: Perforation of gallbladder and intra peritoneal spillage of bile and stones during LC is still a common incident, but are not associated with undesirable events and are not indications for conversion. When spilled bile is properly aspirated by peritoneal irrigation the operative and post-operative courses are similar to those of patients without spillage of gallbladder contents.